A five-equation model based global ale method for compressible multifluid and multiphase flows. (15th January 2021) - Tian, Baolin; Li, Li
Highlights: A mixing cell closure mode was derived in Lagrangian formulation with clear and direct physical meaning. A global ALE(Arbitrary Lagrangian-Eulerian) method was developed for both multifluid and multiphase flows. The proposed method is conservative and non-oscillatory for multi-material flows. Abstract: In this work, a mixing cell closure model was derived in a Lagrangian formulation based on the hypothesis of isentropic compression or expansion. The proposed closure model is used to construct a five-equation model for the simulation of multifluid and multiphase flows. Thereafter a global ALE(Arbitrary Lagrangian-Eulerian) method was developed for the five-equation model. The five-equation based ALE method is a two-stage ALE method, including a Lagrangian phase and a rezone-remap phase. In the first phase, the model equation was discretized with a cell-centered Lagrangian scheme, and a multifluid Riemann solver was proposed by extending traditional Riemann solver to mixed cells with different materials. The five-equation based ALE method can be used to simulate multi-material flows with large deformation, which is a challenge for many traditional ALE methods. Moreover, it can be used to simulate multiphase flows. A series of multi-material and multiphase test problems were simulated with the five-equation based ALE method, and numerical results agree well with exact solutions and reference results.